Evaluation of choroidal thickness, retinal vascular caliber, and nerve fiber layer thickness in idiopathic interstitial pneumonia - Ugurlu, Erhan; Pekel, Gokhan; Cengiz, Betul; Bozkurt, Kerem; Altinisik, Goksel (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2017)
Background: Idiopathic interstitial pneumonia (IIP) is a subtype of interstitial lung disease. Hypoxia and oxidative stress that take a role in IIP, are also thought to affect ocular structures. Objectives: In this study, our aim was to evaluate the retinal nerve fiber layer thickness, choroidal thickness and retinal vessel diameter using the Spectral-domain optical coherence tomography (SD-OCT) in participants with IIP. Material and method: A total of 35 subjects with IIP were evaluated. The ocular parameters of patients with IIP were compared with that of 35 age-sex matched healthy volunteers. All subjects underwent respiratory function testing and carbon monoxide diffusion test. Arterial blood gas analysis was performed to determine the hypoxic state. In addition to SD-OCT measurements, all participants underwent a standard ophthalmic examination including visual acuity assessment, biomicroscopy, air-puff tonometry and retinal examination. Results: The mean retinal arteriolar caliber (RAC) was 89.5±5.5 μm in the IIP group and 94.3±6.9 μm in the control group (p=0.002). The mean retinal venular caliber (RVC) was 131.5±11.2 μm in the IIP group and 125.2±9.2 μm in the control group (p=0.01). The mean inferior quadrant retinal nerve fiber layer (RNFL) thickness was 127.5±19.4 μm in the IIP group and 140.1±13.8 μm in the control group (p=0.003). Conclusion: The IIP may affect retinal vessels and nerve fiber layer. The diameter of the retinal venules was larger and the diameter of the retinal arterioles was smaller in the IIP patients when compared to the healthy controls. The inferior quadrant RNFL was significantly thinner in the IIPgroup.